Transnationalization of service industries: an empirical analysis of the determinants of foreign direct investments by transnational service corporations - Li, Jiatao... et al (UN New YorkUS, 1993)
Investigates the determinants of foreign direct investment by transnational service corporations in both developed and developing countries. Foreign-direct-investment decisions of 210 of the largest transnational service corporations in eleven service industries are analysed over the period 1976 to 1986. Examines major factors affecting foreign direct investment in services viz. market size, home-country business presence, cultural distance, government regulations, competitive advantages of service industries, oligopolistic reaction, industry concentration, tradability of services and growth of firm size.